Effect of flyash on liquefaction behaviour of sand-bentonite mixture - Keramatikerman, M.; Chegenizadeh, Amin; Nikraz, Hamid; Sabbar, A. (Japanese Geotechnical Society, 2018)
This manuscript analyses the effect of flyash (FA) on liquefaction behaviour of sand-bentonite (SB) mixture by conducting a series of undrained monotonic triaxial compression tests. The effect of adding 5% bentonite and three FA contents (i.e., 3, 5 and 7) at three relative densities (i.e., 10, 20, and 30%) on liquefaction behaviour of clean sandy soil were investigated. The analysis on shearing responses of the SB mixtures showed that the addition of bentonite reduced the ultimate deviatoric stress. Investigation on the effect of FA on shearing behaviour of SB specimens showed that the addition of FA caused a greater peak deviatoric stress and the formation of a non-flow behaviour. Furthermore, analysis of the effect of relative density showed that the peak deviatoric stress (qmax) is greater at a higher relative density in particular in FA treated specimens. The results showed that addition of FA into SB mixtures, caused more stability for the samples at peak state while the stress ratio value (q/p') increased and the state parameter (?) reduced. A similar behaviour observed for slope factor (Mcs) in stress-strain plane (q-p'), and for slope of critical state line (?cs), and intercept (Gcs) in compression plane (e-p'). Finally, investigation on the liquefaction behaviour of the specimens based on brittleness index (IB) showed that the untreated soil and SB specimens have a lower liquefaction strength than the FA treated specimens.